Contact time and take-off speed relationship in determining height of jump in jumping badminton smash - Rambely, A. S.; Abas, W. A. B. W (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The paper investigates the relationship between the foot contact time with the ground during the planting of foot phase and the horizontal and vertical velocities before take-off to determine an attainable height of jump during a jumping smash performance. World class badminton players were chosen as subjects. Results showed that contact time was found to be about 0.22 s to generate the greatest forward momentum and there was a greater need to convert the horizontal velocity to vertical velocity, as the vertical velocity determines the attainable height of jump.